2014
DOI: 10.4103/0973-1482.136639
|View full text |Cite
|
Sign up to set email alerts
|

Malignant lymphoma in Eastern India: A retrospective analysis of 455 cases according to World Health Organisation classification

Abstract: Incidence of follicular lymphoma is lower compared to western studies and mixed cellularity is most common subtype of HL unlike nodular sclerosis subtype in western world. Burkitt's type NHL though is the most common subtype of childhood ML in many studies but in our study T cell NHL is the most common type of childhood ML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
19
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 12 publications
13
19
2
Order By: Relevance
“…Extranodal marginal zone B-Cell Lymphomas (MALT) which accounted for 3 cases (8.57%) and Nodal marginal zone B-Cell Lymphoma which accounted for 2 cases (5.71%). These findings were similar with the findings of mandel et al & Roy et al [12,18] Among the T-cell lymphomas, anaplastic large cell lymphoma (ALCL) was the most common subtype forming 5 cases (41.67%) of all NHL. T-cell lymphoblastic lymphoma accounted for 3cases (25%), peripheral T-cell lymphomas (NOS) accounted for 3 cases (25%) and Angioimmunoblastic lymphoma accounted for 1 case (8.33%) of all NHL cases respectively.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Extranodal marginal zone B-Cell Lymphomas (MALT) which accounted for 3 cases (8.57%) and Nodal marginal zone B-Cell Lymphoma which accounted for 2 cases (5.71%). These findings were similar with the findings of mandel et al & Roy et al [12,18] Among the T-cell lymphomas, anaplastic large cell lymphoma (ALCL) was the most common subtype forming 5 cases (41.67%) of all NHL. T-cell lymphoblastic lymphoma accounted for 3cases (25%), peripheral T-cell lymphomas (NOS) accounted for 3 cases (25%) and Angioimmunoblastic lymphoma accounted for 1 case (8.33%) of all NHL cases respectively.…”
Section: Discussionsupporting
confidence: 82%
“…Our study showed 81% of Non Hodgkins Lymphoma and 19% of Hodgkins Lymphoma which was similar to the findings of (Manoj et al & mandal et al) 76.3% and 23.7% respectively. [11,12] . The incidence of Hodgkins lymphoma was more lower in some Asian countries like Japan (7%), Thailand (8.5%) and china (6.6%).…”
Section: Discussionmentioning
confidence: 99%
“…A review of other published studies from NAF/ME/IN (Castella et al , ; Almasri et al , ; Isikdogan et al , ; Abdel鈥怓attah & Yassine, ; Sahni & Desai, ; Akhtar et al , ; Goldman et al , ; Ameen et al , ; Mozaheb et al , ; Yaqo et al , ; Arora et al , ; Otrock et al , ; Mondal et al , ) generally showed relative frequencies of NHL subtypes similar to our study (Table ). The most common lymphoma in all of these studies was DLBCL, ranging from 31% in Egypt (Abdel鈥怓attah & Yassine, ) to 59% in the United Arab Emirates (UAE) (Castella et al , ), with most studies reporting a frequency above 40%.…”
Section: Discussionmentioning
confidence: 87%
“…A particularly high frequency of T鈥怢BL was observed in India (7路2%), significantly higher than in NA (2%). Studies from other countries in the region (Table ) have shown variable relative frequencies of T鈥怢BL ranging from 0路8% to 8路6% (Castella et al , ; Almasri et al , ; Isikdogan et al , ; Sahni & Desai, ; Goldman et al , ; Ameen et al , ; Yaqo et al , ; Arora et al , ; Mondal et al , ). Interestingly, two other studies from India also reported high relative frequencies of T鈥怢BL, of 6路9% (Sahni & Desai, ) and 8路6% (Mondal et al , ), whereas another study reported a frequency of 2路2% (Arora et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation